The Great Fossil Enigma: The Search for the Conodont Animal - E. N. Anderson (Ethnobiology Letters, 2013)
Review of The Great Fossil Enigma: The Search for the Conodont Animal. Simon J. Knell. 2012. Indiana University Press, Bloomington. Pp. 440. $45.00 (cloth), 25 b & w illustrations. ISBN 9780253006042.